The Interpretation of OPAC service in the Library of Universitas Airlangga - Dyah Puspitasari Srirahayu, DYAH (Digital Commons, 2019)
The application of OPAC service in the library has been going on for a long time. This service has given many advantages to users as a quick and accurate tool for information retrieval. Even so, not all people use OPAC service; in fact, previous researches reveal that the application of OPAC service is decreasing. Therefore, this study aims to find out what is the interpretation of OPAC by the users of the library of Universitas Airlangga, thus gaining a deeper analysis on the matter. The method used for this study is qualitative method, with purposive sampling as the technique to determine informants, while the techniques of data collection are done by in-depth interview and observation. The result of this study will be explained using Encoding-Decoding concept from Stuart Hall, which produces three position typologies of the users who used OPAC service in the university library. Those three positions are Dominant/hegemonic position where the users understand the meaning directly according to the purpose of OPAC service; Negotiated position reveals the position of the users who are quite understand the aim of OPAC service; and Oppositional position in which the users who strongly object the library’s purpose to provide a quick and accurate information provider through OPAC service.